IMPROVEMENT OF SURVEILLANCE SYSTEMS FOR ARTIFICIAL STRUCTURES ON THE RAILWAYS - Bokarev, S. O.; Yashnov, O. M.; Pribytkov, S. S.; Sliusar, O. V. (Science and Transport Progress, 2005)
The article examines the questions of improving supervision and diagnostic techniques of facilities. Natural frequency of superstructure is selected as a primary diagnostic parameter. Modeling of dynamic behavior of a span superstructure has been based on the finite-element method.